Atividade física nos programas de promoção a saúde do homem no Distrito Itaqui Bacanga, São Luís-Ma: opinião de profissionais de saúde e usuários - ARAGÃO, Francisca Bruna Arruda (2018)
The National Policy of Integral Attention to Human Health was a milestone in the promotion of health actions destined to the male user, contrary to other policies destined to women and other minorities. Among the actions that this policy advocates, physical activity plays a fundamental role for this public to have access to health promotion programs. Based in these aspects, the present study object to know the opinions of the professionals and users of the Family Health Strategy (ESF) on actions to promote health and physical activities developed for men in the Itaqui Bacanga District. A total of 119 male patients followed by the health units surveyed and 36 professionals that make up the FHT (minimum staff) who provided direct assistance to the patients participated in the study, through a sample selection for convenience. This research in used two instruments of information collection concerning the professionals of the FHT (interview script) and the male participants (quantitative questionnaire). Based on the results found, with regard to health professionals, it was verified that the assistance to the male user is still slow, since cultural and socioeconomic barriers are still obstacles for the going of the man to the basic units, also it was observed in the testimonials of the professionals , that despite trying to change this reality, the UBS are still seen by the male public as a feminized place. However, we observe that the lack of professional knowledge about PNAISH is a worrying factor, since for adequate care it is important to know all the actions necessary to influence or motivate the demand for health services. Regarding the users, it was observed that the man who does activity has less CNCD (12.9%) than those who are sedentary (34.7%). It is also possible to observe a significant association (p <0.05) between non-physical activity and daily use of medication. Man who does activity uses less medication (12.9%) than those who are sedentary (36.7%). In other crosses, there were no significant associations (p> 0.05) with physical activity, that is, the proportions of the classes of these variables in the group of men who perform physical activity are similar to those in the group that does not perform physical activity. However, although 84.1% were aware of the importance of disease prevention; 84.4% do not participate in any program by the health center. The other important finding was that 99.2% would like to participate in some health program and 86.6% would like to talk about their health, however, of that percentage, 100% are ashamed to talk about it; 54.6% reported work as a difficulty factor to go to the health service. In this sense, it is observed that the male participation is small in the services, for multiple reasons, it can be concluded that there is a need to carry out other studies with the same theme, since the PNAISH is an advance in the health of the man, besides to enable this public to offer an integral and humanized assistance, considering the uniqueness of the masculine universe.